From failure to success: an investigation into managers' criteria for assessing the outcome of IT projects. (6th January 2009) - Kutsch, Elmar; Maylor, Harvey
This paper reports a grounded empirical study into the role of failure recognition in project-based work. The findings show that project managers considered a set of performance measures beyond those of time, cost and quality. Further, they focused on finding elements of success and did not recognise elements of failure in their projects as opportunities for improvement. The implications of these findings are that if a failure is to be a learning point for future success, there needs to be development of an extended set of performance measures including 'failure measures' for projects.